2022
DOI: 10.3390/app12157563
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the Anisotropy of Pedestrian Dynamics: An Empirical Analysis with Artificial Neural Networks

Abstract: Identifying the factors that control the dynamics of pedestrians is a crucial step towards modeling and building various pedestrian-oriented simulation systems. In this article, we empirically explore the influential factors that control the single-file movement of pedestrians and their impact. Our goal in this context is to apply feed-forward neural networks to predict and understand the individual speeds for different densities of pedestrians. With artificial neural networks, we can approximate the fitting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…When we look more closely into the specific structure, it becomes clear that there are also variations depending on the experimental setup. The type of flow, such as uni-, bi-, or multidirectional streams; human factors such as age, gender, height, and culture [3,[18][19][20][21][22][23][24][25][26], or external factors such as restricted visibility [27], different height adjustments due to smoke [28], motivation or instruction [18], temperature [29], sidewalk quality [29,30], rhythm or background music [31,32], or properties of human movement, such as step length and frequency [33][34][35][36][37][38][39], all affect the fundamental diagram. This list is only exemplary and does not claim to be complete.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When we look more closely into the specific structure, it becomes clear that there are also variations depending on the experimental setup. The type of flow, such as uni-, bi-, or multidirectional streams; human factors such as age, gender, height, and culture [3,[18][19][20][21][22][23][24][25][26], or external factors such as restricted visibility [27], different height adjustments due to smoke [28], motivation or instruction [18], temperature [29], sidewalk quality [29,30], rhythm or background music [31,32], or properties of human movement, such as step length and frequency [33][34][35][36][37][38][39], all affect the fundamental diagram. This list is only exemplary and does not claim to be complete.…”
Section: Introductionmentioning
confidence: 99%
“…However, a comparison with data from other cultures and different ages raises the question of which other factors also need to be considered. In [21], using the data from the experiments introduced in [20], Subaih et al have shown that the headway to the front and to the back is important, too. This result suggests that the arrangement by gender has an effect on the distances between pedestrians and must be taken into account in modeling the speed-density relation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation